Antibiotic Susceptibility of Bacterial Isolates Exposed to Anacardium occidentale (Cashew) Ethanol Leaf Extract - Giwa, Oluwamodupe Emmanuel; Oluwafemi, Temitope Nike (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2025)
The antibiotic susceptibility pattern of some bacterial isolates obtained from Rufus Giwa Polytechnic student hostel environment was evaluated and compared with the ethanol leaf extract from Anacardium occidentale using standard methods. The isolates were identified as Bacillus subtilis, B. sphaericus, Klebsiella spp, Coliform, Pseudomonas aeruginosa, Serratia marcescens, Staphylococcus aureus, and Streptococcus pyogenes. The highest total average bacterial count was recorded on Tryptose Soy agar from grey water and surface swab to be 3.28 x 105 and 3.89 x 105 cfu/ml respectively, while isolates on Blood agar samples recorded the lowest average count from grey water and surface swab (3.15 x 102 and 3.15 x 105 cfu/ml). However, bacterial isolates on MacConkney agar, Mannitol Salt Agar, and Pseudomonas agar also recorded significantly high bacterial counts of (4.45 x 105 cfu/ml and 4.56 x 105), (4.65 x 102 and 4.24 x 102) and (4.13 x 103 and 4.02 x 105 ) cfu/ml from grey water and surface swab respectively. The inhibited sensitivity around the extract ranged around 9.25 and 11.57 mm cleared zone. This inhibitory extract showed a similar antimicrobial activity on Staphylococcus aureus and coliform representing a broad-spectrum effect on gram positive and gram- negative bacteria respectively. Staphylococcus aureus also showed an inhibitory zone ranging from 5.52±0.29 to 12.2±0.53 while coliform ranged from 5.91±0.35 to 12.6±0.45 respectively corresponding to the increase in the concentration. Tin layer chromatography showed retention factor index includes 0.97, 0.91, 0.81, 0.56, 0.23 and 0.12. The obtainability and easy access to Anacardium occidental makes it cheap as an alternative medicine in comparison in term of result to commercially available antibiotics that has develop resistant to most pathogens. Screening and documentation of the potent constituent in the extract is important to further concentrate for better inhibitory effectiveness